Вставна новела у структурі постмодерного роману Міли Іванцової «Гра в паралельне читання» - Колінько, Олена; Kolinko, Elena (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті простежується чутливість романного жанру до постмодерних віянь, його здатність до структурної мобільності, зазначаються зміни, що відрізняють його від традиційної форми, з'ясовуються роль і значення вставних новел у будові роману та їх вплив на зміст і форму. The article traces the sensitivity of the novel genre to the postmodern trends, its capability for structural mobility, the changes are mentioned that distinguish it from the traditional form, the role and the importance of built-in stories are distinguished in its construction and its impact on the content and form are examined. It is concluded that the novel by Mila Ivantsova "Playing parallel reading" shows that in the period of global changes i.e. in the era of post-modernism, there are significant processes in a genological paradigm, especially in a novel form, that is the most dynamic and is always in a state of constant renewal.
Built-in Short Story in the Structure of the Post-modernist Novel by Mila Ivantsova "Playing parallel reading"
Keywords: роман; постмодерний роман; novel; post-modernist novel